City of bones - Clare, Cassandra (New York : Margaret K. McElderry Books, 2008)
Suddenly able to see demons and the Darkhunters who are dedicated to returning them to their own dimension, fifteen-year-old Clary Fray is drawn into this bizarre world when her mother disappears and Clary herself is almost killed by a monster.
Wilson's Senior High School, October 2011
School Library Journal, May 2007
Publisher's Weekly, April 2007
Horn Book, October 2007
Bulletin (Center for Children's books), June 2007
Voice of Youth Advocates (V.O.Y.A.), April 2007
Keywords: Demonology -- Juvenile fiction; Supernatural -- Juvenile fiction; Demonology -- Fiction; Supernatural -- Fiction; Fantasy; Demonology -- Fiction; Supernatural -- Fiction; Fantasy fiction; Fantasy fiction